Acid Rain And Well Water Acidification Rate In Industrial Area - Sutanto, Sutanto; Darusman, Latifah K; Anwar, S.; J., Tania (Journal of Science Innovare, 2024)
In the area of Cibinong-Citeureup Bogor has many industries, dusty and there are has been acid rain. About 75.63 % people in this area take well water for drinking. It was studied impact of acid rain for well water degradation in order to know the trend and rate of well water pH change. Preliminary research was done in order to make sure the effect of acid rain to well water using soil column leaching simulation. The main research was done by pH monitoring of acid rain and well water in the specific location. The pH of acid rain was monitored in the first 30 minutes on 12 locations from the year of 1999 to 2009, and the well water pH was measured from the year of 1995 to 2009. The acidity (pH) was measured using pHmeter electronic. The rate of pH change was calculated by first order reaction. The result showed that the well water acidity has uptrend (the pH to be lower). The acid rain has a little impact to the acidity of well water (r = 0.68). The rate of acidity of well water has constant value, k = 0.004 year-1.